Teknik Self Management dalam Pengelolan Strategi Waktu Kehidupan Pribadi Yang Efektif - Elvina, Siska Novra (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2019)
This article describes all theories or aspects related to behavior counseling, self management techniques in time management. The research method used in this article is to use theoretical studies. Humans can only control time with activities that are carried out in the passage of time passed. Many people have realized that, but still often just pass the time. On the other hand, there are those who do not realize the time they have just missed. Behavior such as neglect of time that is passed away can be detrimental to every individual in carrying out their activities. Every behavior that has become a habit can be changed through the process of learning from the environment. Behavioral counseling is a model of counseling based on learning theory that focuses on individual behavior to help clients learn new behavior in solving problems. In implementing Behavior Counseling can use self management techniques. Self-management (self management) is a procedure where individuals regulate their own behavior. Based on the results that have been obtained, that every wrong behavior can be changed through behavior counseling using self management techniques. This research is very important, because we can learn how to manage time effectively so that the time we have does not go away.